Farm-Produced Plant Biostimulant: Case Study with Passion Fruit - Luciano P. Canellas; Natália A. Canellas; Dariellys Martinez-Balmori; Rakiely M. Silva; Raul C. C. Rosa; Fabio L. Olivares (Agronomy)
Plant biostimulants (PBs) have been considered the new wave for ecological intensification and sustainability, but are they sustainable? They increase nutrient use efficiency and reduce the impact of abiotic stress in plants. However, commercially available PBs based on humic substances are obtained using non-renewable sources of organic matter. At the same time, the microbial inoculants include a discussion of the properties of microorganisms and formulation design, as well as standards of purity and process control. Farmers depend on biological inputs like others to generate additional income for agribusiness. We produced a composite PB using humic substances isolated from vermicompost with KOH 5% and microbial consortia of plant growth-promoting bacteria (H. seropedicae, G. diazotrophicus, Bacillus spp.) grown in a simple medium with molasses and fishmeal as sources of C and N, respectively, in a homemade reactor at 37 °C for 36 h. The on-farm PB was applied directly in a passion fruit trial, and plant health and yield were monitored. The plants treated with the PB showed decreased visual symptoms of pests and diseases concurrent to higher activities of the enzymes used to monitor the induction of the plant resistance system (1,3-β glucanase, peroxidase, and phenylalanine ammonia-lyase). Plants treated with the PB yielded more than 50% more passion fruit than the control in soil with natural low fertility, fertilized with vermicompost. It is possible to produce PBs directly on the farm, leveraging locally available resources and simple technologies to sustainably enhance plant health and productivity.